Wireless Algorithms, Systems, and Applications 8th International Conference, WASA 2013, Zhangjiajie, China, August 7-10, 2013. Proceedings - Ren, Kui.; Liu, Xue.; Liang, Weifa; Xu, Ming.; Jia, Xiaohua; Xing, Kai.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 7th International Conference on Wireless Algorithms, Systems, and Applications, WASA 2013, held in Zhangjiajie, China, in August 2013. The 25 revised full papers presented together with 18 invited papers were carefully reviewed and selected from 80 submissions. The papers cover the following topics: effective and efficient state-of-the-art algorithm design and analysis, reliable and secure system development and implementations, experimental study and testbed validation, and new application exploration in wireless networks.
Improving Particle Filter with Better Proposal Distribution for Nonlinear Filtering Problems -- Performance Evaluation with Control Channel on the Coexistence Scenario of TD-LTE and LTE-FDD -- Buffer Occupation in Wireless Social Networks -- Efficient Identity-Based Encryption without Pairings and Key Escrow for Mobile Devices -- A Network Forensics System for Information Leak Events -- Maximum Independent Set of Links with a Monotone and Sublinear Power Assignment -- An Auction Mechanism for Resource Allocation in Mobile Cloud Computing Systems -- A Novel Delay-Resilient Remote Memory Attestation for Smart Grid -- A Source-Relay Selection Scheme with Power Allocation for Asymmetric Two-Way Relaying Networks in Underground Mines -- Performance Analysis of Broadcast in Multi-channel Multi-radio Wireless Mesh Networks -- SAFE: A Strategy-Proof Auction Mechanism for Multi-radio, Multi-channel Spectrum Allocation -- A Context-Aware MAC Protocol for VANETs -- A Balance Storage Nodes Assignment for Wireless Sensor Networks -- A Trustworthiness Evaluation Method for Wireless Sensor Nodes Based on D-S Evidence Theory -- UCOR: An Unequally Clustering-Based Hierarchical Opportunistic Routing Protocol for WSNs -- A Quadri-Stage Contention MAC Protocol with Opportunistic Network Coding Support for Underwater Acoustic Networks -- Fast Encryption of JPEG 2000 Images in Wireless Multimedia Sensor Networks -- Evaluating Selective ARQ and Slotted Handshake Based Access in Real World Underwater Networks -- ActiviTune: A Multi-stage System for Activity Recognition of Passive Entities from Ambient FM-Radio Signals -- From Decision Fusion to Localization in Radar Sensor Networks: A Game Theoretical View -- Characterizing the Impact of Non-uniform Deployment of APs on Network Performance under Partially Overlapped Channels -- Patient$1 (Bs Motion Recognition Based on SOM-Decision Tree -- Range-Free Mobile Node Localization Using Static Anchor -- Neighbor Discovery Algorithm Based on the Regulation of Duty-Cycle in Mobile Sensor Network -- Diversity between Human Behaviors and Metadata Analysis: A Measurement of Mobile App Recommendation -- An Urban Area-Oriented Improving Particle Filter with Better Proposal Distribution for Nonlinear Filtering Problems -- Performance Evaluation with Control Channel on the Coexistence Scenario of TD-LTE and LTE-FDD -- Buffer Occupation in Wireless Social Networks -- Efficient Identity-Based Encryption without Pairings and Key Escrow for Mobile Devices -- A Network Forensics System for Information Leak Events -- Maximum Independent Set of Links with a Monotone and Sublinear Power Assignment -- An Auction Mechanism for Resource Allocation in Mobile Cloud Computing Systems -- A Novel Delay-Resilient Remote Memory Attestation for Smart Grid -- A Source-Relay Selection Scheme with Power Allocation for Asymmetric Two-Way Relaying Networks in Underground Mines -- Performance Analysis of Broadcast in Multi-channel Multi-radio Wireless Mesh Networks -- SAFE: A Strategy-Proof Auction Mechanism for Multi-radio, Multi-channel Spectrum Allocation -- A Context-Aware MAC Protocol for VANETs -- A Balance Storage Nodes Assignment for Wireless Sensor Networks -- A Trustworthiness Evaluation Method for Wireless Sensor Nodes Based on D-S Evidence Theory -- UCOR: An Unequally Clustering-Based Hierarchical Opportunistic Routing Protocol for WSNs -- A Quadri-Stage Contention MAC Protocol with Opportunistic Network Coding Support for Underwater Acoustic Networks -- Fast Encryption of JPEG 2000 Images in Wireless Multimedia Sensor Networks -- Evaluating Selective ARQ and Slotted Handshake Based Access in Real World Underwater Networks -- ActiviTune: A Multi-stage System for Activity Recognition of Passive Entities from Ambient FM-Radio Signals -- From Decision Fusion to Localization in Radar Sensor Networks: A Game Theoretical View -- Characterizing the Impact of Non-uniform Deployment of APs on Network Performance under Partially Overlapped Channels -- Patient$1 (Bs Motion Recognition Based on SOM-Decision Tree -- Range-Free Mobile Node Localization Using Static Anchor -- Neighbor Discovery Algorithm Based on the Regulation of Duty-Cycle in Mobile Sensor Network -- Diversity between Human Behaviors and Metadata Analysis: A Measurement of Mobile App Recommendation -- An Urban Area-Oriented Traffic Information Query Strategy in VANETs -- Navigation for Indoor Mobile Robot Based on Wireless Sensor Network -- iMac: Strategy-Proof Incentive Mechanism for Mobile Crowdsourcing -- Social Welfare Maximization in Participatory Smartphone Sensing -- An Optimal Solution for Round Rotation Time Setting in LEACH -- UPC-MAC: A Power Control MAC Protocol for Underwater Sensor Networks -- FMAC for Coexisting Ad Hoc Cognitive Radio Networks -- Effective RSS Sampling for Forensic Wireless Localization -- An Optimal Leakage Detection Strategy for Underground Pipelines Using Magnetic Induction-Based Sensor Networks -- Compressive Data Retrieval with Tunable Accuracy in Vehicular Sensor Networks -- Enforcing Spectrum Access Rules in Cognitive Radio Networks through Cooperative Jamming -- Photo Forensics on Shanzhai Mobile Phone -- Local Information Storage Protocol for Urban Vehicular Networks -- Maximum Independent Set of Links with Power Control -- Sweep-Coverage with Energy-Restricted Mobile Wireless Sensor Nodes -- The Trading between Virtual Mobile Operator and Wireless Service Provider in the Two-Tier Femtocell Network -- Truthful Online Reverse Auction with Flexible Preemption for Access Permission Transaction in Macro-Femtocell Networks -- Social Communications Assisted Epidemic Disease Influence Minimization.s
Keywords: Computer science; Computer Communication Networks; Computer system performance; Computer software; Computer Science; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Information Systems Applications (incl. Internet).; System Performance and Evaluation; Computer Science, general; Computer Science, general